2017
DOI: 10.18520/cs/v113/i02/228-235
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Optimization of Photoanodes and Counter Electrodes of Dye-Sensitized Solar Cells

Abstract: Since 1991, dye-sensitized solar cells (DSSCs) have emerged as a potential alternative to conventional silicon photovoltaics for conversion of solar energy to electric power, due to their advantages of costeffectiveness, sustainability and ease of fabrication among others. As the functioning of DSSCs depends on the sum of the functions of individual components, effective understanding and optimization of these components is important for the optimization of the device itself. Therefore, this review focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The high potential peak which can be ascribed to the Reaction (1). Moreover, the low potential peak which is mainly related to performance of DSSCs is attributed to the Reaction (2) [ 80 ]. 2I 3 − ↔ 3I 2 + 2e − 3I − ↔ I 3 − + 2e − …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high potential peak which can be ascribed to the Reaction (1). Moreover, the low potential peak which is mainly related to performance of DSSCs is attributed to the Reaction (2) [ 80 ]. 2I 3 − ↔ 3I 2 + 2e − 3I − ↔ I 3 − + 2e − …”
Section: Resultsmentioning
confidence: 99%
“…The high potential peak which can be ascribed to the Reaction (1). Moreover, the low potential peak which is mainly related to performance of DSSCs is attributed to the Reaction (2) [80]. During the process of preparing CEs with doctor blade method, we found that with 5 wt% PtCo and 12 wt% PtCo, surface tension of liquid is large and not easy to spread, so it cannot be wetted and converged on conductive glass.…”
Section: Cyclic Voltammetry Analysismentioning
confidence: 98%